Protecting bank deposits - Garcia, G. G.; International Monetary Fund (Washington, D.C. : International Monetary Fund, 1997)
Although the special importance of banks to a country's economy might seem to make the insurance of their deposits unquestionably worthwhile, the reality is not that simple.
"Draws on material originally contained in IMF Working Paper 96/83, 'Deposit insurance : obtaining the benefits and avoiding the pitfalls,' by Gillian Garcia ... Alfred Imhoff prepared the present version"--Pref.
"July 1997"--T.p. verso.
Keywords: Deposit insurance; Banks and banking